IL-23 blockade with guselkumab potentially modifies psoriasis pathogenesis: rationale and study protocol of a phase 3b, randomised, double-blind, multicentre study in participants with moderate-to-severe plaque-type psoriasis (GUIDE) - Eyerich, Kilian; Weisenseel, Peter; Pinter, Andreas; Schäkel, Knut; Asadullah, Khusru; Wegner, Sven; Muñoz-Elias, Ernesto J.; Bartz, Holger; Taut, Friedmann J. H.; Reich, Kristian (BMJ open, 2021)
Background Guselkumab is an interleukin (IL)-23 pathway blocker with proven efficacy in patients with moderate-to-severe plaque psoriasis. Early intervention with guselkumab may result in changes to the clinical disease course versus later intervention. - Methods and analysis Here we present the rationale and design of a phase 3b, randomised, double-blind, multicentre study (GUIDE), comparing treatment effects of guselkumab in patients with short (≤2 years) or longer (>2 years) duration of plaque-type psoriasis, measured from first appearance of psoriatic plaques. Participants achieving skin clearance (Psoriasis Area and Severity Index (PASI)=0) by week 20 and maintaining complete clearance at week 28 visit (‘super-responders’ (SRe)) will be randomised to continue approved maintenance dosing every 8 weeks (q8w) versus an investigational maintenance dosing interval of 16 weeks (q16w) until week 68. Primary endpoint: proportion of participants in the q8w vs q16w arms with absolute PASI <3 at week 68. Participants with PASI <3 at week 68 will be withdrawn from guselkumab treatment for up to 48 weeks. Participants not achieving SRe criteria (non-SRe) will remain in the study with q8w guselkumab dosing through week 68. Additional to serum samples obtained from all patients, skin biopsies and whole-blood samples will be taken from SRe and non-SRe participants at various time points in optional substudies. Analyses include: genetics; immunophenotyping (fluorescence-activated cell sorting); gene and protein expression profiling; immunohistology. By merging clinical endpoints with mechanistic findings, this study aims to elucidate how IL-23 blockade with guselkumab can modify the disease course by altering molecular and cellular drivers that cause relapse after treatment withdrawal, particularly among SRe. - Ethics and dissemination Approval obtained from ethics committee Medical Council Hamburg, Germany (PVN5925). GUIDE is compliant with the Declaration of Helsinki. - Trial registration number Registered at ClinicalTrials.gov (NCT03818035). All primary endpoint results (prespecified analyses) will be submitted to peer-reviewed, international journals within 18 months after primary completion date.